2017
DOI: 10.1111/nicc.12304
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric intensive care nurses' decision‐making around gastric residual volume measurement

Abstract: BackgroundMeasuring gastric residual volume (GRV) to guide enteral feeding is a common nursing practice in intensive care units, yet little evidence supports this practice. In addition, this practice has been shown to potentially contribute to inadequate energy delivery in intensive care, which remains a problem in critically ill children.. AimsWe aimed to explore paediatric intensive care nurses' decision-making surrounding this practice. MethodsA cross-sectional electronic survey in a single mixed general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…These include gastric residual volumes (GRV), vomiting, diarrhea, abdominal distention and pain/discomfort, and the use of serum lactate [41,46]. However, evidence to support each of these as an indicator of feeding intolerance is weak or absent, and in critically ill children, a multitude of non-feedrelated factors can produce these signs and symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include gastric residual volumes (GRV), vomiting, diarrhea, abdominal distention and pain/discomfort, and the use of serum lactate [41,46]. However, evidence to support each of these as an indicator of feeding intolerance is weak or absent, and in critically ill children, a multitude of non-feedrelated factors can produce these signs and symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…We did not formally appraise the quality of these papers, as our aim was to describe the definition and use of the term feeding intolerance. A further 32 papers were review or discussion papers [n = 6] [2, 6,13,18,46,47], surveys [n = 5] [16,40,41,43,44], research papers which support this review but are not included in papers which defined feeding intolerance [n = 19] [3, 8, 11, 12, 14, 15, 17, 24, 25, 27, 30-32, 36, 38, 39, 42, 49], and guidelines [n = 2] [4,26] where feeding intolerance was mentioned or discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, these are nurses not following or being unaware of current guidelines. Although our study focused on practices in adult ICUs, paediatric ICU (PICU) nurses were also shown to frequently measure GRV (Tume et al, ). In a single‐centre survey in the United Kingdom with 91 participating nurses, 58% measured GRV before every feed, 27% every 4 h and 17% every 6 h. The majority of participants (84%) stated that they would be worried or very worried if GRV would not be measured routinely.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, when decision-making is based on volume, clinicians fail to consider the impact of gastric secretions produced during the digestion process. 23 This study has limitations. First, as with any survey, responses may not reflect actual practice.…”
Section: Discussionmentioning
confidence: 92%